Comparison of Local Corticosteroids versus Plasma Rich Protein for Management of Rotator Cuff Tendinopathy - Umair Saleem, Muhammad Kamran Afzal, Muhammad Saqib, Muhammad Fareed Azam, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Rotator cuff (RC) tendinopathy accounts for majority of shoulder conditions in adult patients resulting in shoulder pain and occupational disability. Recently injections around joint area typically including corticosteroid, local anaesthetic, opioid and a non-steroidal anti-inflammatory drug (NSAID) have been used for treatment of such conditions. Aim: To compare the efficacy of ultrasound-guided injections of platelet-rich plasma (PRP) and corticosteroids on clinical and functional assessment. Study design: Double blind randomize controlled trial Place and duration of study: Department of Orthopaedic Surgery, POF Hospital, Wah Cantt and Izzat Ali Shah Hospital Wah Cantt 1st January 2020 to 31st January 2021. Methodology: Sixty patients was tendinitis or partial tear of rotator cuff tendon, had pain for >3 months and >40 years old were enrolled. Patients were randomly divided into two groups; Group A patients were administered corticosteroid injections, the Depo-medrol 40mg and Group B patients were administered PRP injections. Results: The mean age was 55.9±4.3 years in group A while in group B mean age was 55.2±5.2 years. After treatment the mean VAS scores were 4.39±1.8 in group A and in group B was 3.27±1.5. In group A after treatment mean ROM was 28.34±4.6 and in group B mean ROM was 32.64±5.2 (P<0.001) considered significant. Conclusion: Corticosteroids use limitation of being contraindicated in few individuals and associated risk of tendon rupture. The use of PRP among patients with rotator cuff tendinopathy as results showed marked improvement in pain intensity and range of movements after PRP administration.